2005
DOI: 10.1007/s11242-004-2594-9
|View full text |Cite
|
Sign up to set email alerts
|

Boiling in Porous Media: Model and Simulations

Abstract: We present a modelization of the heat and mass transfers within a porous medium, which takes into account phase transitions. Classical equations are derived for the mass conservation equation, whereas the equation of energy relies on an entropy balance adapted to the case of a rigid porous medium. The approximation of the solution is obtained using a finite volume scheme coupled with the management of phase transitions. This model is shown to apply in the case of an experiment of heat generation in a porous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Darcy's laws and Fick's laws are, respectively, taken into account to model the diffusion of the mixture (dry air and vapour) and the liquid, and the diffusion of the vapour in the mixture. See Bénard et al (2005) for a modelling of the heat and mass transfers within a porous medium, which takes into account phase transitions (without dry air). Assuming isothermal conditions, the model consists of two balance equations: dry air mass and water species mass (both liquid and vapour).…”
Section: Field Equation For Nondeformable Partially Saturated Porous mentioning
confidence: 99%
See 1 more Smart Citation
“…Darcy's laws and Fick's laws are, respectively, taken into account to model the diffusion of the mixture (dry air and vapour) and the liquid, and the diffusion of the vapour in the mixture. See Bénard et al (2005) for a modelling of the heat and mass transfers within a porous medium, which takes into account phase transitions (without dry air). Assuming isothermal conditions, the model consists of two balance equations: dry air mass and water species mass (both liquid and vapour).…”
Section: Field Equation For Nondeformable Partially Saturated Porous mentioning
confidence: 99%
“…In the nonlinear case studied in this paper, the forward problem has been modelled by using finite volume method for space discretization, and finite differences for time integration. See Eymard et al (2000) for a presentation of the finite volume methods, and Bénard et al (2005) for application to thermal and hydraulical diffusion including phase changes. The identification method is based on the solution of an inverse problem.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Stefan problem is based on a conservation equation, it has been shown that the use of the finite volume method, which satisfies a local conservation property, accurately respects the location of the moving boundary (see [4,15]). …”
Section: The Continuous Problemmentioning
confidence: 99%
“…It is generally assumed that below a certain moisture content of approximately 5 vol.% no spalling will occur [1,2]. Numerous heat and mass transfer models have been used to predict the moisture transport and its consequences on the strength and permeability of the concrete [3][4][5][6][7][8]. However, these models are only of use if they can be validated.…”
Section: Introductionmentioning
confidence: 99%